Verbal compression as the implementation of universal tendency of compensative processes in the lingual world - Diachok, Natalia V.; Kuvarova, Olena K.; Prystaiko, Tamara S.; Kirkovska, Inga S.; Semak, Liudmyla A. (Linguistics and Culture Review, 2021)
The objective of the research is to describe mental and verbal primary and secondary (modern) compressive transformations. Main research methods are represented by the descriptive and structural ones making it possible to demonstrate characteristic aspects of univerb- and composite-formation (including abbreviation) as the processes corresponding to the essence of verbal compression. A tendency to compensative processes in speech and language is represented by the formations capable of complete substituting of the analytical primary names of objects, signs, and actions of the reality. In other words, a compensative process implies, apart from its main task, – balancing of the number of verbal units, – contraction of sounding duration and writing form of those units, i.e., substitution of analytical, multicomponent, nominative formations for the synthetic, monocomponent ones; that means saving time and space as the means of information conveyance. That tendency originates in the Common Slavic period. Univerbs and abbreviations, including telescopisms, are real forms of nominative units of analytical representation (word combinations) and potential alternative forms of synthetic (verbal) nominative units as the same time.